Clinical and immunological responses of dust mite sensitive, atopic dogs to treatment with sublingual immunotherapy (SLIT). Issue 2 (8th January 2016) - DeBoer, Douglas J.; Verbrugge, Maria; Morris, Mary
Abstract : Background: Sublingual immunotherapy (SLIT) has been reported to be beneficial in people with atopic dermatitis (AD) and dust mite sensitivity. Evaluation of this therapy has not been reported in spontaneous canine AD. Objectives: The objective of this study was to preliminarily evaluate the effectiveness of an established SLIT protocol, as used in human patients, in dogs with AD. Animals: Ten dust mite sensitive dogs with spontaneous AD. Methods: Dogs underwent a 6 month open trial of SLIT concurrently with decreasing dose oral methylprednisolone. Clinical evaluations and quantitative serum anti‐mite IgE and IgG levels were performed every 2 months. Results: Mean methylprednisolone use from the first 2 months of the study to the final 2 months declined from 10.2 to 4.3 mg/kg/2 months ( P < 0.001, Student's paired t ‐test); at 6 months, four dogs required no oral corticosteroid administration. Over the course of the study, median Canine Atopic Dermatitis Extent and Severity Index (CADESI)‐03 scores declined from 76.5 to 59; median pruritus scores declined from 65 to 37 ( P < 0.02 and P < 0.01, respectively; Wilcoxon signed‐rank test). Pre‐ and post‐SLIT intradermal test scores for mite allergen were not significantly different over time. Median Dermatophagoides farinae (DF)‐specific IgE levels declined significantly from 150.2 × 10 3 AU/mL to 3.6 × 10 3 AU/mL ( P < 0.05). Concurrently, median DF‐specific IgG levels increased from 18.5 × 10 6 AU/mL to 3923.4 × 10 6 AU/mL ( P < 0.05; Wilcoxon signed‐rank tests). Conclusions and clinical importance: SLIT treatment produced clinical improvement in dogs with dust mite‐associated AD and was associated with serological changes supporting this improvement. Further studies in larger numbers of dogs and those with polysensitization are warranted. Abstract : Background – Sublingual immunotherapy (SLIT) has been reported to be beneficial in people with atopic dermatitis (AD) and dust mite sensitivity. Evaluation of this therapy has not been reported in spontaneous canine AD.Objectives – The objective of this study was to preliminarily evaluate the effectiveness of an established SLIT protocol, as used in human patients, in dogs with AD.Conclusions and clinical importance – SLIT treatment produced clinical improvement in dogs with dust mite‐associated AD and was associated with serological changes supporting this improvement. Further studies in larger numbers of dogs and those with polysensitization are warranted.